Strain variation in the mycobacterium tuberculosis complex : its role in biology, epidemiology and control - Gagneux, Sebastien (Springer, 2017)
Until about 10 years ago, the general view in the field was that Mycobacterium tuberculosis, the causative agent of human tuberculosis was a "clone" with insufficient natural sequence variation between clinical strains to be considered biologically and epidemiologically "relevant". This view has now changed quite dramatically thanks to the -omics revolution, particularly the advent of next generation DNA sequencing. Large-scale comparative genomic studies over the last few years have revealed that M. tuberculosis clinical strains are more genetically diverse than appreciated previously. Moreover, an increasing number of experimental and epidemiological studies are showing that this genetic diversity also translates into important phenotypic variation. Taken together, these findings have led to a paradigm shift, such that currently phylogenetic diversity among M. tuberculosis clinical strains is being considered in the development of new tools to combat tuberculosis. The purpose of this book is to bring together a series of contributions from some of the most influential groups working on various aspects of M. tuberculosis diversity, and which through their work have contributed to the this paradigm shift. This includes authors focusing on the evolution of M. tuberculosis in relation to other members of the M. tuberculosis complex adapted to animals, the co-evolution between M. tuberculosis and humans, the phenotypic consequences of strains diversity both from an experimental and epidemiological point of view, the ecology and evolution of drug resistant tuberculosis, the diversity and evolution of the BCG vaccine strains, and the use of mathematical modelling to study strain diversity and drug resistance in human tuberculosis. No such book has ever been published, and given the paradigm shift described above, this book will be a valuable resource both for established researchers as well as new scientists, clinicians and public health officials joining the growing field of tuberculosis research.
Keywords: Mycobacterium tuberculosis -- Genetic aspects.; Mycobacterium tuberculosis -- Epidemiology.; elektronické knihy; electronic books